The Influence Of Leadership And Communication Styles On The Work Motivation Of Employees In PT Dipo Internasional Pahala Automotive Medan Sandpaper - Damanik, Evo Marisi Tumpal; Sebayang, Immanuel Edy Suranta; Simarmata, Bengettua; Girsang, Tonggo Sangap Timbul (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
In the context of the current era of globalization, leadership and communication styles have a central role in influencing motivation in the organizational environment. Increasingly complex and uncertain challenges emphasize the need for leaders to have adaptability to manage change. The right leadership style, accompanied by effective communication, can have a positive impact on individual motivation within the organization. This study aims to explore the effect of leadership style and communication on work motivation at PT Dipo International Pahala Automotive Medan Amplas. The approach in this study is descriptive quantitative, primary data sources obtained through questionnaires. And the population in this study amounted to 168 respondents, with a sample size of 118 respondents. The calculation results show that, leadership style partially affects employee work motivation, obtained t count (4,473) > t table (1,658) with a significance of 0.000 <0.05, then H0 is rejected and H1 is accepted, meaning that there is a positive and significant influence between leadership style on employee work motivation. While the communication variable obtained t count (9.011) > t table (1.658) with a significance of 0.000 <0.05, then Ho is rejected and H2 is accepted, meaning that there is a positive and significant influence between communication on employee work motivation. Simultaneously leadership style and communication have an effect on work motivation, obtained f count 87.645> f table 3.08 and sig 0.000, then H0 is rejected and H3 is accepted, meaning that leadership style and communication simultaneously have a positive and significant effect on employee work motivation.